Tingkat Kepuasan Petani Terhadap Benih Kentang Varietas Baru “X” Sebagai Bahan Baku Industri Pengolahan - Putra, Ivangga Dwi; Setiawan, Iwan; Suminartika, Eti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Imports of raw materials for the potato industry show fluctuations and an increasing trend. As local breeders are unable to provide the demand for industrial seed potatoes, about 4,000 tons of industrial seed potatoes are still imported by Indonesia every year, which is one of the reasons for the low domestic production of industrial potatoes. To meet demand, measures are needed to increase industrial seed potato production.  A domestic university has been working to develop a new and improved industrial potato variety. Industrial potato variety "X" is an example of a superior variety that was successfully produced. The objective of this study was to measure farmers' satisfaction with the newly introduced industrial potato variety "X". Quantitative descriptive methodology was used in this study to determine the level of farmer satisfaction with seed potato variety "X" and the degree of congruence between the importance and implementation of the features of industrial seed potatoes as seen by farmers. Potato resistance to pests and diseases, harvest age, tuber size produced, tuber shape, flesh color and texture, storability, and productivity levels are the eight characteristics of industrial potatoes that will be used in this study. Data were examined through the application of Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) techniques. IPA findings indicated that traits related to harvest age and resistance to pests and diseases should be improved first. The results of the CSI assessment show that farmers are satisfied with industrial potato seed "X" with a CSI value of 79.68%, which falls into the satisfied criteria. This is because the high productivity and large tuber size are in line with farmers' expectations and interests.  Other advantages of "X" seed potatoes are their oval shape, high starch content, low moisture content, and color/texture that allows them to be processed into a variety of processed products, such as chips and french fries.